أثر إدارة المعرفة على الأداء الوظيفي دراسة حالة في المؤسسسة التجارية اتصالات الجزائر-مداوروش-سدراتة- - مروة شارف; وردة بن خدومة (My University, 2022)
This study aimes to identify the inpzct of knowledge administration on the fonctionnel performance of employés at the algerian comunications of Souk ahras.In this study ;we adopted the analtyic descriptive approach.The inpact of knowledge managements processes was examined which include ,knouledeg diagnosis,knouledge acquisition ,knouledge generation, knouledge development and application of knouledge in fungtionah perfomance.Arandom sample of (30)singel of all categories working in the institution was tested.the SPSS program was also used to analyse the data and to test the assumption.The résulte show that, there is asmall inpact of the indépendant variables on the dépendent variable.No statistically signifiant différences existe between the response of the study sanple about the inpact of the knouledge administration on functional performance that refer to the variables as ;Age ;sexy ;scientifique level ;years of Works and fonctionnel categoeery. .................................... تهدف هذه الدراسة إلى التعرف على أثر إدارة المعرفة في الأداء الوظيفي لدى العاملين بالمؤسسة التجارية اتصالات الجزائر-مداوروش-سدراتة-واعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي،وقد تم اختبار أثر عمليات إدارة المعرفة والمتمثلة في :تشخصي المعرفة،اكتساب المعرفة،توليد المعرفة،تخزين المعرفة،تطوير المعرفة،تطبيق المعرفة،في الأداء الوظيفي،حيث اعتمدنا على المسح الشامل باخذ كافة الفئات العاملة بالمؤسسة،واستعملنا برنامج التحليل في تحليل البيانات واختبار الفرضيات،وبينت النتائج أن هناك تأثير ضغيق للمتغيرات المستقلة )SPSS( الإحصائي على المتغير التابع،كما أنه لا توجد فروق ذات دلالة إحصائية بين إجابات عينة الدراسة حول أثر عمليات إدارة المعرفة في الأداء الوظيفي تعود إلى متغيرات السن ،الجنس،المستوى العلمي،المنصب الوظيفي،الخبرة المهنية